Education-focused academics in pursuit of third-space visibility: a five-step process - Antonios Kaniadakis; Fiona Denney (Journal of Learning Development in Higher Education)
Education-focused academics were introduced to enhance the quality of education and assist universities in addressing sector metrics that would place them favourably within an increasingly competitive environment. We argue that they form part of third-space staff in universities as their work remains mostly hidden as part of a ‘taken-for-granted’ infrastructure. Following the infrastructure metaphor, we propose a five-step process in the career development of education-focused academics, from early career to educational leaders, that would bring visibility to their work and that of other third-space occupants. Making third-space work visible on the personal, organisational, and sectoral levels will ensure real impact and fulfilment of its disruptive and transformative potential for Higher Education Institutions (HEIs).